Anelastic and Plastic Properties of Microcrystalline Magnesium with Ceramic Nanoparticles - Z. Trojanová (Canadian Institute of Mining, Metallurgy and Petroleum, 2006)
Mg micropowders generated by gas atomisation of a magnesium melt with argon were mixed and ball milled with ceramic nanoparticles prepared by laser-induced gas phase reaction. The materials were then hot extruded. Specimens were deformed in tensile as well as compression tests at temperatures between 20 and 300 °C at a constant initial strain rate. The flow stress is significantly influenced by the test temperature. The yield stress decreases with temperature. This decrease and the flat character of the stressstrain curves at elevated temperatures indicate possible contributions of softening processes. The materials studied exhibit high-damping characteristics. The results are analysed and possible mechanisms are discussed.